Amitriptyline at low-dose and titrated for irritable bowel syndrome as second-line treatment (The ATLANTIS trial): protocol for a randomised double-blind placebo-controlled trial in primary care - Alderson, Sarah L.; Wright-Hughes, Alexandra; Ford, Alexander C.; Farrin, Amanda; Hartley, Suzanne; Fernandez, Catherine; Taylor, Christopher; Ow, Pei Loo; Teasdale, Emma; Howdon, Daniel; Guthrie, Elspeth; Foy, Robbie; et al. (Current controlled trials in cardiovascular medicine, 2022)
Background Irritable bowel syndrome (IBS) is a common functional bowel disorder that has a considerable impact on patient quality of life and substantial societal and health care resource costs. Current treatments are often ineffective. Tricyclic antidepressants have shown promise in secondary care populations but their effectiveness in a primary care setting remains unclear. Methods ATLANTIS is a randomised, multi-centre, parallel-group, two-arm, double-blind, placebo-controlled trial of low-dose amitriptyline as a second-line treatment for IBS in primary care. Participants will be invited by letter, or recruited opportunistically, from general practices in three regions of England (West Yorkshire, Wessex, and West of England) and screened for eligibility. A total of 518 adult patients with IBS, who are symptomatic despite first-line therapies, will be randomised 1:1 to amitriptyline or identical placebo for 6 months. Treatment will commence at a dose of 10 mg (or one placebo tablet) daily at night, with dose titration up to a maximum of 30 mg at night, depending on side effects and response to treatment. Participant-reported assessments will be conducted at baseline and 3, 6, and 12 months post-randomisation. The primary objective is to determine the effectiveness of amitriptyline, compared with placebo, in improving participant-reported global symptoms of IBS at 6 months (using the IBS Severity Scoring System). Secondary outcomes include relief of IBS symptoms, effect on IBS-associated somatic symptoms (Patient Health Questionnaire-12), anxiety and depression (Hospital Anxiety and Depression Scale), ability to work and participate in other activities (Work and Social Adjustment Scale), acceptability and tolerability of treatment, self-reported health care use, health-related quality of life (EQ-5D-3L), and cost-effectiveness. A nested, qualitative study will explore patient and general practitioner experiences of treatments and trial participation, including acceptability, adherence, unanticipated effects, and implications for wider use of amitriptyline for IBS in primary care. Discussion Determining the clinical and cost-effectiveness of low-dose amitriptyline as a second-line treatment for IBS in primary care will provide robust evidence to inform management decisions. Trial registration ISRCTN ISRCTN48075063 . Registered on 7th June 2019.